Aquaculture in Kenya: Present State and Development Trends - MATVEEVA Natalia Fedorovna (Ученые записки Института Африки Российской академии наук)
At present, about half of the total amount of fish and seafood consumed in the world is grown in artificial conditions, while in the early 2000s its share was 30%, and in the 1980s it did not exceed 7%. This trend is formed against the background of depletion of natural marine and freshwater bio-reserves. Overexploitation of some of their species, primarily fish, has actually reached the verge of sustainable reproduction or even exceeds this objective limit beyond which no production is possible without compromising the ecological state of the aquatic biological environment. At the same time, the population’s demand for products containing the most suitable balance of proteins, “right” fats, vitamins and amino acids is increasing more and more. One of their main sources is water bio-reserves.